Soil respiration in temperate forest ecosystems of Mexico and its relationship with organic carbon - Cruz-Sánchez, Yadihra; López-Teloxa, Leticia C.; Gómez Diaz, Jesús D.; Monterroso-Rivas, Alejandro I. (Instituto de Ecología, A.C., 2021)
Forest ecosystems play an influential role in the global carbon cycle, decreasing the greenhouse effect through capture and fixation processes. Many studies have analyzed the interaction between organic carbon and soil respiration, but it is important to increase the information in temperate ecosystems. The main goal of the present study was to evaluate the spatial-temporal variation of soil respiration and organic carbon in soil and to assess the influence of environmental factors on soil respiration. Soil organic carbon data for four stands, determined by vegetation type and three different depths were obtained using an organic carbon analyzer. Soil respiration was sampled with an infrared gas analyzer in four stands and four seasons of the year (May 2019 - January 2020). In addition, soil temperature, soil humidity data, and climatological information were taken from two meteorological stations located within the study area. Soil organic carbon ranged from 163.09 Mg ha-1 to 207.45 Mg ha-1 storing more carbon in stands of mixed forests. Soil respiration fluctuated between 39.27 Mg ha-1 yr-1 and 67.96 Mg ha-1 yr-1 with higher amounts emitted in pure or natural forests. Soil organic carbon correlated negatively with soil respiration. Changes in soil respiration suggest a strong dependence on the environmental scenario due to an interaction of the climate and vegetation type, varying on the characteristics of the time of year and the stand.